Efficacy, safety and tolerability of rozanolixizumab in patients with chronic inflammatory demyelinating polyradiculoneuropathy: a randomised, subject-blind, investigator-blind, placebo-controlled, phase 2a trial and open-label extension study - Querol, Luis; De Sèze, Jérôme; Dysgaard, Tina; Levine, Todd; Rao, T Hemanth; Rivner, Michael; Hartung, Hans-Peter; Kiessling, Peter; Shimizu, Saori; Marmol, Dominika; Bozorg, Ali; Colson, Anny-Odile; et al. (Journal of neurology, neurosurgery, and psychiatry, 2024)
BACKGROUND: Chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) is a peripheral nerve disorder characterised by weakness and sensory loss. We assessed the neonatal Fc receptor inhibitor rozanolixizumab for CIDP management. METHODS: CIDP01 (NCT03861481) was a randomised, subject-blind, investigator-blind, placebo-controlled, phase 2a study. Adults with definite or probable CIDP receiving subcutaneous or intravenous immunoglobulin maintenance therapy were randomised 1:1 to 12 once-weekly subcutaneous infusions of rozanolixizumab 10 mg/kg or placebo, stratified according to previous immunoglobulin administration route. Investigators administering treatment and assessing efficacy, and patients, were blinded. The primary outcome was a change from baseline (CFB) to day 85 in inflammatory Rasch-built Overall Disability Scale (iRODS) score. Eligible patients who completed CIDP01 entered the open-label extension CIDP04 (NCT04051944). RESULTS: In CIDP01, between 26 March 2019 and 31 March 2021, 34 patients were randomised to rozanolixizumab or placebo (17 (50%) each). No significant difference in CFB to day 85 in iRODS centile score was observed between rozanolixizumab (least squares mean 2.0 (SE 3.2)) and placebo (3.4 (2.6); difference -1.5 (90% CI -7.5 to 4.5)). Overall, 14 (82%) patients receiving rozanolixizumab and 13 (76%) receiving placebo experienced a treatment-emergent adverse event during the treatment period. Across CIDP01 and CIDP04, rozanolixizumab was well tolerated over up to 614 days; no clinically meaningful efficacy results were seen. No deaths occurred. CONCLUSIONS: Rozanolixizumab did not show efficacy in patients with CIDP in this study, although this could be due to a relatively high placebo stability rate. Rozanolixizumab was well tolerated over medium-to-long-term weekly use, with an acceptable safety profile.
Keywords: Humans; lidé středního věku; Polyradiculoneuropathy, Chronic Inflammatory Demyelinating; Immunoglobulins, Intravenous; Female; Aged; dospělí; výsledek terapie; FC RECEPTOR; senioři; lidé; humanizované monoklonální protilátky; MOVEMENT DISORDERS; RANDOMISED TRIALS; Adult; Antibodies, Monoclonal, Humanized; ženské pohlaví; Single-Blind Method; Male; Middle Aged; Treatment Outcome; MYASTHENIA; jednoduchá slepá metoda; intravenózní imunoglobuliny; mužské pohlaví; NEUROMUSCULAR; chronická zánětlivá demyelinizační polyneuropatie